Respuesta :

Step by step explanation:

Step 1:

[tex]2(x-6) + 6 = 4x - 4[/tex]

Step 2:

[tex]⇒2x - 12 + 6 = 4x - 4[/tex]

Step 3:

[tex]⇒2x - 6 = 4x - 4[/tex]

Step 4:

[tex]⇒ - 6 + 4 = 4x - 2x[/tex]

Step 5:

[tex]⇒2x = - 2[/tex]

Step 6:

[tex]⇒x = \dfrac{ - 2}{2} [/tex]

Step 7:

[tex]⇒x = - 1✓[/tex]

[tex]◈verification◈[/tex]

Step 1:

[tex]2( - 1-6) + 6 = 4( - 1) - 4[/tex]

Step 2:

[tex]⇒2( - 7) + 6 = - 4 - 4[/tex]

Step 3:

[tex]⇒ - 14 + 6 = - 8[/tex]

Step 4:

[tex]⇒ - 8 = - 8[/tex]

[tex]†hence \: vertified†[/tex]